PTU-038 Should a Plastic or a fully Covered Metal Stent be Placed at Index ERCP when a Patient Presents with Jaundice Due to a Malignant Distal Biliary Stricture?. (4th June 2013) - McClements, D; Mahmood, S; Whelan, P; Psarelli, E-E; Smart, H L; Evans, J; Lombard, M; Sarkar, S
Abstract : Introduction: Traditionally plastic stents (PS) are inserted at the index ERCP to treat obstructive jaundice from malignant distal biliary strictures. However, with the development of fully covered metal stents (C-SEMS), this approach is now debated and practise at the Royal Liverpool Hospital (RLH) has now changed towards preference for C-SEMS in this clinical scenario. This of course has cost implications as C- SEMS are 15–20 times more expensive than plastic stents. The aim of this study is to determine the benefit of C-SEMS over PS placement, to answer the question which stent should be inserted at the index ERCP if a patient presents with malignant obstructive jaundice Methods: A retrospective audit was performed of patients undergoing ERCP with placement of plastic or SEMS for obstructive jaundice due to malignant distal biliary strictures at the RLH between March 2007 and December 2012. Clinical history, course and outcomes from MDT documents, electronic patient records and the endoscopy database were recorded on a standardised proforma. Only PS and C-SEMS insertion at the index ERCP were included. Results: Of 147 patients identified, 72 were excluded (bare metal stents or partially covered metal stents placed). This left 43 in PS group and 32 in C-SEMS group. 21 patients underwent surgical resection; 17 within PS and 4 within C-SEMS. Of these no patient with C-SEMS but 3 (18%) patients with plastic stents required re-intervention prior to surgery due to stent dysfunction. In the remaining palliative patients (PS: n = 26 and C-SEMS: n = 28), 19 with plastic stents (73%) and 3 patients with SEMS (7%) required endoscopic re-intervention due to stent dysfunction (p < 0.001). Median time to re-intervention was 32 days (range 5–58) for PS and 25 days (range 25–38.5) for C-SEMS (p = 0.394). Overall, PS at the index ERCP only offered definitive stenting in only 53% (23/43) compared to 91% (29/32) by C-SEMS (p = 0.001). Conclusion: Placement of a fully covered SEMS (C-SEMS) at index ERCP offered a definitive procedure in majority of patients compared to plastic stent (PS) which was just over half. Whilst C-SEMS significant more expensive than PS, this increased cost may be potentially be offset by the reduction in the need for repeat ERCP intervention and subsequent stent insertions. A full cost analysis is currently being undertaken. Disclosure of Interest: None Declared